2018
DOI: 10.1080/09540121.2018.1466982
|View full text |Cite
|
Sign up to set email alerts
|

HIV-associated cognitive disorders in perinatally infected children and adolescents: a novel composite cognitive domains score

Abstract: Accurate assessment of HIV-associated cognitive disorders in perinatally infected children and adolescents is challenging. Assessments of general intellectual functioning, or global cognition, may not provide information regarding domain-specific strengths and weaknesses, and may therefore fail to detect, impaired trajectories of development within particular cognitive domains. We compare the efficacy of global cognitive scores to that of composite cognitive domain scores in detecting cognitive disorders in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…The study found the prevalence of any cardiac, respiratory or neurocognitive impairment in PHIV+ participants was significantly higher than in HIV− participants. Similar findings of individual system involvement have been reported in other studies of adolescents with perinatally acquired HIV with a high prevalence of cardiac, respiratory, neurocognitive or less commonly renal impairment .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The study found the prevalence of any cardiac, respiratory or neurocognitive impairment in PHIV+ participants was significantly higher than in HIV− participants. Similar findings of individual system involvement have been reported in other studies of adolescents with perinatally acquired HIV with a high prevalence of cardiac, respiratory, neurocognitive or less commonly renal impairment .…”
Section: Discussionsupporting
confidence: 89%
“…The study found the prevalence of any cardiac, respiratory or neurocognitive impairment in PHIV+ participants was significantly higher than in HIVÀ participants. Similar findings of individual system involvement have been reported in other studies of adolescents with perinatally acquired HIV with a high prevalence of cardiac, respiratory, neurocognitive or less commonly renal impairment [5,36,37]. Neurocognitive impairment occurring most commonly, is perhaps the most concerning morbidity, impacting on PHIV+ adolescents as it influences all spheres of health including treatment adherence and school performance.…”
Section: Discussionsupporting
confidence: 84%
“…We standardized WISC or WAIS raw subtests into Wechsler norm scores (with a mean of 10 and standard deviation [SD] of 3) and into scale scores (mean 100, SD 15) using age- and sex-adjusted Dutch norm standards from test manuals[20, 21]. We converted Beery VMI raw scores into t-scores (with a mean of 50 and SD of 10)[24], and standardized TMT and RAVLT raw scores into Z-scores, as no appropriate Dutch reference values were available[22, 23, 25]. We calculated Z-scores based on the mean and SD of the control group [25].…”
Section: Methodsmentioning
confidence: 99%
“…We converted Beery VMI raw scores into t-scores (with a mean of 50 and SD of 10)[24], and standardized TMT and RAVLT raw scores into Z-scores, as no appropriate Dutch reference values were available[22, 23, 25]. We calculated Z-scores based on the mean and SD of the control group [25]. We reverse coded variables in order to align interpretation in the same direction: for all tests lower scores indicate poorer test performance.…”
Section: Methodsmentioning
confidence: 99%
“…A recent meta-analysis found that working memory, executive functioning, and processing speed are the cognitive domains most affected in children and adolescents living with HIV [8]. Sherr et al suggested that since the evidence for HIV-associated cognitive impairment is consistent, children living with HIV should be routinely and regularly monitored for developmental delays and cognitive dysfunction so they can be referred to available intervention [9].…”
Section: Introductionmentioning
confidence: 99%